2008
DOI: 10.1002/fld.1812
|View full text |Cite
|
Sign up to set email alerts
|

Projection method for flows with large local density gradients: Application to dendritic solidification

Abstract: SUMMARYNumerical models of solidification including a mushy zone are notoriously inefficient; most of them are based on formulations that require the coupled solution to the velocity components in the momentum equation greatly restricting the range of applicability of the models. Initial attempts at modeling directional solidification in the presence of a developing mushy zone using a projection formulation encountered difficulties once solidification starts, which were traced to the inability of the method to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…The method has been described earlier in the context of binary alloy solidification [50]. In the present work, appropriate changes are made in the governing equations to apply it for the solidification of multicomponent alloys.…”
Section: Projection Methods For Solving the Momentum Equationmentioning
confidence: 99%
“…The method has been described earlier in the context of binary alloy solidification [50]. In the present work, appropriate changes are made in the governing equations to apply it for the solidification of multicomponent alloys.…”
Section: Projection Methods For Solving the Momentum Equationmentioning
confidence: 99%
“…u * is the intermediate velocity. Following the formulation described by Heinrich et al, [19] the momentum equation can be split into the following steps:…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Westra [18] presented the use of fractional step method in the simulation of freckle defects that occur in directional solidification processes. [18] A large three-dimensional calculation performed by Heinrich et al, [19] showed evidence that significant improvement in efficiency of macrosegregation computations is possible with the use of fractional step method for the solution of the momentum equation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The work by Heinrich et al [9] focuses on the development of a projection method for the simulation of dendritic solidification in flows where large local density gradients are present. The modified projection method used in this work preserves the pressure gradient-body force coupling.…”
mentioning
confidence: 99%